2017
DOI: 10.1063/1.4986961
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and encapsulation of flexible polyelectrolytes in charged spherical vesicles

Abstract: We present a theory of adsorption of flexible polyelectrolytes on the interior and exterior surfaces of a charged vesicle in an electrolyte solution. The criteria for adsorption and the density profiles of the adsorbed polymer chain are derived in terms of various characteristics of the polymer, vesicle, and medium, such as the charge density and length of the polymer, charge density and size of the vesicle, electrolyte concentration and dielectric constant of the medium. For adsorption inside the vesicle, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The system minimizes its potential energy with trivalent counterions-monomer Coulombic attractions, and simultaneously gains additional translational entropy of the released monovalent counterions. 12 13 14…”
Section: Multivalent Counterion Fractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The system minimizes its potential energy with trivalent counterions-monomer Coulombic attractions, and simultaneously gains additional translational entropy of the released monovalent counterions. 12 13 14…”
Section: Multivalent Counterion Fractionmentioning
confidence: 99%
“…The influence of spatial confinement on polyelectrolytes has been extensively investigated. The equilibrium conformation of a highly charged polymer chain confined in a cavity is evidently governed by the interplay between energetic and entropic factors coming from the confinement shape and size relative to the chain length, the chain bending stiffness, the electrostatic interaction between the charged monomers, counterions, and the solvent, as well as their configurational entropy. For short flexible polyelectrolytes confined in a neutral spherical cavity, Kumar and Muthukumar using self-consistent field theory demonstrated that, for a given radius of the spherical cavity and fixed charge density along the backbone of the chain, solvent and small ion entropies dominate over all other contributions to the free energy.…”
mentioning
confidence: 99%
“…Previous theories mainly focus on the adsorption of homopolymer corresponding to the nonselective adsorption. The conventional polymer adsorption problem can be in broad terms rationalized as the tug of war between the attractive interaction of the polymer to the surface and the conformational entropy loss of the polymer as it is being adsorbed to the interface. , As one of the typical examples of nonselective adsorption, the adsorption of homogeneous polyelectrolytes by oppositely charged surfaces has been widely studied, including the effects of solution salinity, charge density, length and stiffness of polyelectrolytes, and curvature and charge distribution of surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…While, for sufficiently strong attraction, the chain was in an adsorbed state. 40 Furthermore, the translocation time was increased due to the confinement effect of the sphere but was reduced by the polymer−sphere attraction. The two effects offset each other at a special polymer−sphere attraction, which is dependent on the sphere size, the polymer length, and the driving force.…”
Section: Introductionmentioning
confidence: 99%